Copy number variation of the SELENBP1 gene in schizophrenia - Mishmar Dan; Belmaker RH; Ebstein Richard; Maier Wolfgang; Ovadia Ofer; Amar Shirly; Agam Galila (Behavioral and Brain Functions, 2010)
Abstract Background Schizophrenia is associated with rare copy-number (CN) mutations. Screening for such alleles genome-wide, though comprehensive, cannot study in-depth the causality of particular loci, therefore cannot provide the functional interpretation for the disease etiology. We hypothesized that CN mutations in the SELENBP1 locus could associate with the disorder and that these mutations could alter the gene product's activity in patients. Methods We analyzed SELENBP1 CN variation (CNV) in blood DNA from 49 schizophrenia patients and 49 controls (cohort A). Since CN of genes may vary among tissues, we investigated SELENBP1 CN in age- sex- and postmortem interval-matched cerebellar DNA samples from 14 patients and 14 controls (cohort B). Since CNV may either be de-novo or inherited we analyzed CNV of the SELENBP1 locus in blood DNA from 26 trios of schizophrenia probands and their healthy parents (cohort C). SELENBP1 mRNA levels were measured by real-time PCR. Results In cohort A reduced CN of the SELENBP1 locus was found in four patients but in none of the controls. In cohort B we found reduced CN of the SELENBP1 locus in two patients but in none of the controls. In cohort C three patients exhibited drastic CN reduction, not present in their parents, indicating de-novo mutation. A reduction in SELENBP1 mRNA levels in the postmortem cerebellar samples of schizophrenia patients was found. Conclusions We report a focused study of CN mutations in the selenium binding-protein1 (SELENBP1) locus previously linked with schizophrenia. We provide evidence for recurrence of decreased CN of the SELENBP1 locus in three unrelated patients' cohorts but not in controls, raising the possibility of functional involvement of these mutations in the etiology of the disease.